THE EMPOWERMENT OF COMMUNITY ECONOMY THROUGH ZAKAT FUNDS (The Analysis on Zakat Fund Management in the National Amil Zakat Agency [BAZNAS], Papua Province) - Husnul Yaqin (JICSA : Journal of Islamic Civilization in Southeast Asian, 2019)
Zakat is one of the pillars of Islam that is required of all Muslims whose wealth has reached Nisab. The collection of BAZNAS zakat funds in Papua province through several stages, namely through socialization to several institutions both public and private and initially originated from UPZ funds in the Jayapura region. Based on the recapitulation of zakat funds in Papua province through BAZNAS in 2018 amounting to Rp. 963,858,000. The distribution of zakat funds carried out by BAZNAS in Papua province is not only a consumptive way but also in a productive way, this is an effective way for community economic empowerment such as assistance distributed to 5 Papuan Muslims, assistance through BKMT, zakat fostered villages (Ambon and Dobonsolo villages) and empowerment of spinach farmers in Mappi district. In addition to the economic empowerment of the people through zakat there is also the provision of scholarship assistance ranging from elementary, junior high, high school and university, in 2018 a number of 23 people have received scholarship assistance through zakat funds. According to the analysis of researchers that the recapitulation of zakat funds shows that between the receipt of Rp. 963,858,000 and expenditure or distribution of Rp. 438,811,500 were unbalanced, so the discovery by the audit team occurred because the distribution was less than 70%.